Scalariform-to-simple transition in vessel perforation plates triggered by differences in climate during the evolution of Adoxaceae - Lens, F; Vos, R; Charrier, G; Van Der Niet, T; Merckx, V; Baas, P; Aguirre Gutierrez, J; Jacobs, B; Chacon Dória, L; Smets, E; Delzon, S; Janssens, S (Oxford University Press, 2016)
Angiosperms with simple vessel perforations have evolved many times independently of species having scalariform perforations, but detailed studies to understand why these transitions in wood evolution have happened are lacking. We focus on the striking difference in wood anatomy between two closely related genera of Adoxaceae, Viburnum and Sambucus, and link the anatomical divergence with climatic and physiological insights.After performing wood anatomical observations, we used a molecular phylogenetic framework to estimate divergence times for 127 Adoxaceae species. The conditions under which the genera diversified were estimated using ancestral area reconstruction and optimization of ancestral climates, and xylem-specific conductivity measurements were performed.Viburnum, characterized by scalariform vessel perforations (ancestral), diversified earlier than Sambucus, having simple perforations (derived). Ancestral climate reconstruction analyses point to cold temperate preference for Viburnum and warm temperate for Sambucus This is reflected in the xylem-specific conductivity rates of the co-occurring species investigated, showing that Viburnum lantana has rates much lower than Sambucus nigra CONCLUSIONS: The lack of selective pressure for high conductive efficiency during early diversification of Viburnum and the potentially adaptive value of scalariform perforations in frost-prone cold temperate climates have led to retention of the ancestral vessel perforation type, while higher temperatures during early diversification of Sambucus have triggered the evolution of simple vessel perforations, allowing more efficient long-distance water transport.